Production and characterization of degradable polyethelene terephthalete using pro-degradant additives, polylactic acid and polylactic acid grafted maleic anhydride - Ashwinder, Chelliah (2019)
Overwhelming environmental concern due to the usage of synthetic plastics such as polyethylene terephthalate (PET) has continuously evoke to the development of biodegradable plastic in the packaging segment. As an effort to promote degradation, pro-degradant (CS), bottle grade polylactic acid (PLA) and functionalised maleated polylactic acid (PLA-g-MA) were blended with polyethylene terephthalate (PET) to study on its properties and degradation behaviour. PET/CS composites, PET/PLA blends with and without compatibilizers were prepared using extrusion and injection molding technique. CS additives were incorporated into PET at a composition of 0.25, 0.5, 0.75 and 1 pph, respectively. In this study the polymer blend was prepared by adding bottle grade PLA composing of 5, 10 and 15 wt % with PET. PET blended with 15 wt % of bottle grade PLA (PLA15) were compatibilized using PLA-g-MA at 2, 4, 6 and 8 wt %, respectively. The formulated samples were then characterized by mechanical properties (tensile and flexural strengths) and thermal characteristics (TGA and DSC). Degradation studies were done using thermo-oxidative and accelerated weathering testing. Attenuated Total Reflectance-Fourier Transform Infrared (ATR-FTIR) spectroscopy and scanning electron microscope (SEM) analysis were performed to study on the molecular structural changes and surface morphologies, while degree of degradation of the polymeric blends were measured using Carbonyl Index. The results indicated that, 0.25CS recorded highest TS, TM, FS and FM compared to pure PET. This showed that addition of CS additives up to 0.25 pph promoted an improved strength and interfacial adhesion in the composites. Thermal studies showed that increasing CS loading from 0.25 to 1 pph reduced the thermal stability of PET, while enthalpy and crystallinity of the composites reduced with increasing CS loading amount in PET. Degradation studies revealed an uneven growth around the carbonyl region of all the samples in the FTIR spectrum upon thermal exposure except for 0.25CS composite sample. However, reduced CI reading (less than 2.6) on all the composite samples interprets absence of degradation in the samples. The increasing addition of bottle grade PLA improved mechanical properties of PET. PLA15 achieved the maximum TS, TM, FS and FM, respectively compared to PET. Nevertheless, addition of PLA-g-MA into PLA15 has resulted in reduced TS, TM, FS and FM. Thermal studies showed that PET/PLA blends with and without PLA-g-MA have undergone a single step decomposition and increasing loading effect of PLA and PLA-g-MA have reduced the thermal stability of PET favoring for degradation to take place. As for the degradation studies, growing carbonyl region of the PLA15 blend after thermal exposure along with increasing CI reading and surface appearance stipulates the degradation process. Likewise, increasing addition of PLA-g-MA in PLA15 blends was observed to promote degradation compared to a compatibilized effect in the PET/PLA blends. Conclusively, blending of bottle grade PLA with PET increases the added value of the polymeric blend with regards to its properties and susceptibility towards degradation.